Frequent genes in rare diseases: panel-based next generation sequencing to disclose causal mutations in hereditary neuropathies - Dohrn, Maike F.; Kotzaeridou, Urania; Korenke, Christoph (Journal of neurochemistry, 2017)
Hereditary neuropathies comprise a wide variety of chronic diseases associated to more than 80 genes identified to date. We herein examined 612 index patients with either a Charcot-Marie-Tooth phenotype, hereditary sensory neuropathy, familial amyloid neuropathy, or small fiber neuropathy using a customized multigene panel based on the next generation sequencing technique. In 121 cases (19.8%), we identified at least one putative pathogenic mutation. Of these, 54.4% showed an autosomal dominant, 33.9% an autosomal recessive, and 11.6% an X-linked inheritance. The most frequently affected genes were PMP22 (16.4%), GJB1 (10.7%), MPZ, and SH3TC2 (both 9.9%), and MFN2 (8.3%). We further detected likely or known pathogenic variants in HINT1, HSPB1, NEFL, PRX, IGHMBP2, NDRG1, TTR, EGR2, FIG4, GDAP1, LMNA, LRSAM1, POLG, TRPV4, AARS, BIC2, DHTKD1, FGD4, HK1, INF2, KIF5A, PDK3, REEP1, SBF1, SBF2, SCN9A, and SPTLC2 with a declining frequency. Thirty-four novel variants were considered likely pathogenic not having previously been described in association with any disorder in the literature. In one patient, two homozygous mutations in HK1 were detected in the multigene panel, but not by whole exome sequencing. A novel missense mutation in KIF5A was considered pathogenic because of the highly compatible phenotype. In one patient, the plasma sphingolipid profile could functionally prove the pathogenicity of a mutation in SPTLC2. One pathogenic mutation in MPZ was identified after being previously missed by Sanger sequencing. We conclude that panel based next generation sequencing is a useful, time- and cost-effective approach to assist clinicians in identifying the correct diagnosis and enable causative treatment considerations.
Gesehen am 11.07.2018